Proposta de implementação de melhorias na gestão de estoque em uma distribuidora de gêneros alimentícios em Manaus - Vale, Larici Darlem Aguiar (Brasil, 2022)
The present study aimed to propose improvements in inventory management to achieve positive results for the company in question. The specific objectives show the importance of inventory management, analysis of the logistics area and the definition of the tools that will be used to improve the inventory management process. The Brainstorming and Ishikawa Diagram tools were applied to perform the diagnosis and in the action plan the 5W2H tool and the Two Drawer System. According to the results obtained, stock problems, difficulties due to the layout, absence of a trained team responsible for the logistics area and the lack of investment in information technology are scored. The conclusion shows that inventory management is essential for the company's good functioning and business sustainability.